Perbedaan Produksi Ibu Nifas Pada Metode SPEOS (Stimulasi Pijat Endorphin Oksitosin Dan Sugestif) Dan Metode Marmet Di Wilayah Kerja Puskesmas Karang Pule Tahun 2019 - Luh Yunita Yunita; Ni Nengah Arini Murni; mutiara rachmawati suseno (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2019)
In order to achieve success in exclusive breastfeeding care is needed for postpartum care in the first days of post partum to help maximize breast milk production. There are various ways that can be done to help increase milk production by using certain massage techniques, especially in the back area such as the SPEOS Method (Endorphin, Oxytocin and Suggestive Massage Stimulation) and the Marmet Technique. The purpose of this study is knowing the differences in the SPEOS Method (Stimulation of Endorphin, Oxytocin and Suggestive Massage) with the Marmet Technique on the milk production of postpartum mothers in the working area of ​​Karang Pule Health Center. This study uses quasi experimental with a post test only design with control group. This research was conducted in April 2019. The study population was all postpartum mothers in the working area of ​​Karang Pule Health Center. The research sample was 34 people. Data analysis using Independent T-test. The characteristics of this study which postpartum mothers were mostly aged 20-35 years with 88.2% presentation, the education level of most senior high schools with a presentation of 47.1%, most mothers did not work with presentations at 76.5% and mostly multiparous parity that is equal to 82.4%. After a statistical test using Independent T-Test significance value (p) of 0.043 <0.05 means that there is a difference between the use of the SPEOS method and the Marmet Technique. The Conclusion this study there is a difference between the SPEOS Method and the Marmet Technique of Breast milk Production in the work area of ​​Karang Pule Health Center